Realizing HOPE: The Ethics of Organ Transplantation From HIV-Positive Donors - Christine M. Durand; Dorry L. Segev; Jeremy Sugarman (2016)
The HIV Organ Policy Equity (HOPE) Act now allows transplantation of organs from HIV-positive living and deceased donors to HIV-positive individuals with end-stage organ disease in the United States. Although clinical experience with such transplants is limited to a small number of deceased-donor kidney transplants from HIV-positive to HIV-positive persons in South Africa, unprecedented HIV-positive-to-HIV-positive liver transplantations and living-donor kidney transplantations are also now on the horizon. Initially, all HIV-positive-to-HIV-positive transplantations will occur under research protocols with safeguards and criteria mandated by the National Institutes of Health. Nevertheless, this historic change brings ethical opportunities and challenges. For HIV-positive individuals needing an organ transplant, issues of access, risk, and consent must be considered. For potential HIV-positive donors, there are additional ethical challenges of privacy, fairness, and the right to donate. Careful consideration of the ethical issues involved is critical to the safe and appropriate evaluation of this novel approach to transplantation.